2019
DOI: 10.1080/08998280.2019.1668668
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled epoprostenol utilization pattern after implementation of an administration policy

Abstract: Epoprostenol, a pulmonary vasodilator, is used to reduce pulmonary artery pressure. Its inhaled administration results in ventilation and perfusion matching with oxygenation improvement. Epoprostenol is used as treatment for various conditions, particularly acute respiratory distress syndrome (ARDS) and pulmonary arterial hypertension. In 2018, Baylor University Medical Center implemented a policy for inhaled epoprostenol utilization aimed at standardizing clinical practice. This study analyzed epoprostenol ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…36 Overall, 71% of the patients with ARDS responded to iEPO therapy with an increase in median P/F ratio from 70 to 140. 36…”
Section: Inhaled Prostaglandinsmentioning
confidence: 91%
See 4 more Smart Citations
“…36 Overall, 71% of the patients with ARDS responded to iEPO therapy with an increase in median P/F ratio from 70 to 140. 36…”
Section: Inhaled Prostaglandinsmentioning
confidence: 91%
“…Collier et al reported thrombocytopenia occurring in 29% and 28% of ARDS and non-ARDS patients, respectively, and Fuller et al found 3 studies reported thrombocytopenia, anemia, or transfusion requirements. 22,36 In contrast, Van Heerden et al reported no effects on platelet aggregation. 50…”
Section: Inhaled Prostaglandinsmentioning
confidence: 99%
See 3 more Smart Citations